Distribution of IOP and its relationship with refractive error and other factors: the Anyang University Students Eye Study - Ma, Dandan; Sun, Yunyun; Li, Shi-Ming; An, Wen-Zai; Hu, Jian-Ping; Cao, Kai; Yang, Xiao-Hui; Lin, Cai-Xia; Guo, Ji-Yuan; Li, He; Fu, Jing; Wang, Ningli (International journal of ophthalmology, 2021)
AIM: To investigate the distribution of intraocular pressure (IOP) and its relationship with refractive error and other factors in university students from Anyang, China. METHODS: A university-based study was conducted. Subjects were invited to complete ophthalmic examinations, including visual acuity, noncontact tonometry (NCT), cycloplegic autorefraction, and ocular biometry. Univariable and multivariable analyses were used to evaluate the associations between IOP and other factors. Only data from right eyes were used in analysis. RESULTS: A total of 7720 subjects aged 16 to 26 years old were included, and 2834 (36.4%) of the participants were male. The mean IOP of the right eye for all subjects was 15.52±3.20 mm Hg (95%CI: 15.45, 15.59). Using multivariate linear regression analysis, IOP was found to correlate significantly with younger age (P<0.001; standardized regression coefficient β, -0.061; regression coefficient β, -0.139; 95%CI: -0.18, -0.09), higher myopic refractive error (P=0.044; standardized β, -0.060; regression coefficient β, -0.770; 95%CI: -0.15, -0.002), higher central corneal thickness (P<0.001; standardized β, 0.450; regression coefficient β, 0.044; 95%CI: 0.04, 0.05), and shorter axial length (AL; P<0.001; standardized β, -0.061; regression coefficient β, -0.163; 95%CI: -0.25, -0.07). CONCLUSION: This study described the normal distribution of IOP. In Chinese university students aged 16-26y, higher IOP is associated with younger age, higher myopic refractive error, higher thickness of the central cornea, and shorter AL.